Characterization Of Pneumatic Artificial Muscle System In An Opposing Pair Configuration - Tang, Teng Fong; Chong, Shin Horng; Tan, Ming Hui; Chan, Chun Yuan; Sato, Kaiji (Penerbit Universiti Teknikal Malaysia Melaka, 2016)
Pneumatic artificial muscle (PAM) is a pneumatic actuator that commonly used in the biomimetic robotic devices in rehabilitation applications due to its advantageous in high power-to-weight ratio and high degree of safety in use characteristics. Several techniques exist in the literature for the PAM system modeling, and these include theoretical modeling, phenomenological modeling and empirical modeling. This paper focuses on explaining the experimental setup of an opposing pair configuration of PAM system, and gives an analysis of the pneumatic muscle system dynamic in the theoretical modeling. The simulated dynamic model is compared with the actual PAM system for the validation in the open-loop step and sinusoidal positioning responses and pressures. It is concluded that the simulation result is verified and agreed with the actual system.